2014
DOI: 10.1586/1744666x.2014.891439
|View full text |Cite
|
Sign up to set email alerts
|

B-cell hyperactivity in primary Sjögren's syndrome

Abstract: Primary Sjögren's syndrome (pSS) is characterized by mononuclear inflammatory infiltrates and IgG plasma cells in salivary and lacrimal glands which lead to irreversible destruction of the glandular tissue and is accompanied by sensation of dryness of mouth and eyes. B cells play a central role in the immunopathogenesis and exhibit signs of hyperactivity. Hyperactivity of B cells is the consequence of the coordinated and integrated action of stimulation of the B-cell receptor, CD40 and toll-like receptors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 164 publications
5
92
0
2
Order By: Relevance
“…Studies that have investigated the pathophysiological mechanisms of pSS have also revealed the significant effect of BAFF on the development of pSS (10,11) . Overproduction of BAFF in transgenic mice has been shown to lead to pathological findings resembling those observed in pSS (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have investigated the pathophysiological mechanisms of pSS have also revealed the significant effect of BAFF on the development of pSS (10,11) . Overproduction of BAFF in transgenic mice has been shown to lead to pathological findings resembling those observed in pSS (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of exocrine glands is accompanied by periductal mononuclear infiltration of these glands, mainly by CD4 + T cells and B cells. Involvement of B cells in pSS pathogenesis is further illustrated by the presence of autoantibodies directed against SS-A/Ro and/or SS-B/La, elevated levels of rheumatoid factor (RF), hypergammaglobulinemia, elevated levels of Bruton's tyrosine kinase in B cells and a significantly increased risk of Non-Hodgkin B cell lymphoma, predominantly mucosa-associated lymphoid tissue (MALT) lymphoma [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Chronic expression of type I IFN also may also influence the function of glandular tissue, for example by promoting apoptosis of the epithelial cells or loss of integrity of the epithelium and consequently xerostomia. Irrespective of the fact whether the pSS patients exhibit high type I or type II IFN activity (i.e.…”
Section: Editorialmentioning
confidence: 99%